Resolvin E3 attenuates allergic airway inflammation via the interleukin‐23‐interleukin‐17A pathway. Issue 11 (30th August 2019) - Sato, Makiko; Aoki‐Saito, Haruka; Fukuda, Hayato; Ikeda, Hiroyuki; Koga, Yasuhiko; Yatomi, Masakiyo; Tsurumaki, Hiroaki; Maeno, Toshitaka; Saito, Tsugumichi; Nakakura, Takashi; Mori, Tetsuya; Yanagawa, Masataka; et al.
Abstract : We investigated the effects of resolvin E (RvE) 1, RvE2, and RvE3 on IL‐4‐ and IL‐33‐stimulated bone marrow‐derived dendritic cells (BMDCs) from house dust mite (HDM)‐sensitized mice. We also investigated the role of RvE3 in a murine model of HDM‐induced airway inflammation. In vitro, BMDCs from HDM‐sensitized mice were stimulated with IL‐4 and IL‐33 and then treated with RvE1, RvE2, RvE3, or vehicle. RvE1, RvE2, and RvE3 suppressed IL‐23 release from BMDCs. In vivo, RvE3 administrated to HDM‐sensitized and challenged mice in the resolution phase promoted a decline in total numbers of inflammatory cells and eosinophils, reduced levels of IL‐23 and IL‐17 in lavage fluid, and suppressed IL‐23 and IL‐17A mRNA expression in lung and peribronchial lymph nodes. RvE3 also reduced resistance in the lungs of HDM‐sensitized mice. A NanoBiT β‐arrestin recruitment assay using human embryonic kidney 293 cells revealed that pretreatment with RvE3 suppressed the leukotriene B4 (LTB4)‐induced β‐arrestin 2 binding to LTB4 receptor 1 (BLT1R), indicating that RvE3 antagonistically interacts with BLT1R. Collectively, these findings indicate that RvE3 facilitates the resolution of allergic airway inflammation, partly by regulating BLT1R activity and selective cytokine release by dendritic cells. Our results accordingly identify RvE3 as a potential therapeutic target for the management of asthma.—Sato, M., Aoki‐Saito, H., Fukuda, H., Ikeda, H., Koga, Y., Yatomi, M., Tsurumaki, H., Maeno, T., Saito, T., Nakakura, T., Mori, T., Yanagawa, M., Abe, M., Sako, Y., Dobashi, K., Ishizuka, T., Yamada, M., Shuto, S., Hisada, T. Resolvin E3 attenuates allergic airway inflammation via the interleukin‐23‐interleukin‐17A pathway. FASEB J. 33, 12750–12759 (2019). www.fasebj.org